# Oliver Lehmann ( 75 ) study question number 61

Hi, I am needing assistance on answering #61 from Oliver Lehmann 75 practice questions. I unserstand that there was a variance but I do not "see" how the formula EAC = BAC - CV was  derived. Thanks...

http://www.oliverlehmann.com/pmp-self-test/75-free-questions.htm

You are performing Earned value technique on your project.

After budget approval, an additional and unexpected cost item has been identified, which made the project more expensive some weeks ago. The item has meanwhile been paid by the project team, and it is expected that for the remaining duration of the project, costs will be as budgeted.

In this case, which is the best formula to calculate EaC (Estimate at Completion)?

A. EaC = BaC - CV
B. EaC = BaC / CPI
C. EaC = AC + BtC / CV
D. You can not compute the EaC.

The anaswer is listed as 'A' with the explanation of "PMBOK® Guide 4th Edition, pp 182 (CV = EV - AC) and 184 (EAC = AC + BAC - EV)"

### It is a straight

It is a straight explanation...........

To the date you have CV in your project ( some extar cost over that budget ) and you consider that future performance will be as per budget

in that case your Estimate at Completion will be Actual cost so far + Budget of Remaining work ( BAC - EV)

= AC + BAC - EV

= BAC - (EV-AC)

= BAC - CV

Swetketu PAtel, PMP

### I know this response is 6

I know this response is 6 years after your reply, but Swetketu Patel doesn't actually answer the question. Instead he restates the answer without any explanation. Can anyone provide a mathematical explanation why AC + (BAC - EV) = BAC - (EV - AC)?

### @cdef: Swetketu Patel

@cdef: Swetketu Patel explained correctly. According to PMBOK 5th page 224, if the future work will be accomplished at the planned rate, use EAC = AC + BAC - EV = BAC - EV + AC = BAC - (EV - AC) = BAC - CV

Chau Nguyen, PMP PMI-RMP PMI-SP LIMC

### Yes, I understand that EAC

Yes, I understand that EAC for atypical variance is AC + BAC - EV, which is all that is relevant from the table on page 224. I understand how you can rearrange the equation to BAC - EV + AC.  What no one has explained is how or why you switch the signs to get BAC - EV - AC.

Is it simply this?

1. CV = EV - AC
2. -CV = - EV + AC
3. So if BAC - EV + AC =
4. BAC + (-EV + AC) =
5. BAC + (-CV) =
6. BAC - CV

### yes, it's simple like you

yes, it's simple like you mentioned :)